Piil Pesenggiri: A Concept of Political Power in Lampung Culture - Robi Cahyadi Kurniawan (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2017)
Power is the main focus of political science, so far the concept of power that exists in Indonesia comes from the conception of western cultural thought, especially Europe, which influenced the thinking of the thinkers of the era of Greece, Rome, and medieval Europe. After the reform and era after 2000, Indonesian thinkers tried to offer the concept of power based on local wisdom based on local culture. So that emerged local concepts of politics and power. This paper attempts to relate the principles of the local culture of Lampung piil pesenggiri in the context of contemporary politics today, especially in the election, including things mystical. The method used in this research/writing by using qualitative methods with secondary data sources and literature study. The result in the level of the concept piil pesenggiri be ideal, but the level is still questionable practice.